Peningkatan Kesiapan Sekolah Siaga Bencana melalui Pelatihan Siswa Kader Sekolah Siaga Bencana di SMPN 1 Cimalaka - Hikmat Pramajati; Nunung Siti Sukaesih; Emi Lindayani; Ahmad Purnama; Reni Nuryani; Heri Ridwan (Universitas Mathla'ul Anwar Banten, 2020)
IMPROVING DISASTER PREPAREDNESS SCHOOL READINESS THROUGH TRAINING OF DISASTER PREPARED SCHOOL CADRE STUDENTS AT SMPN 1 CIMALAKA. Natural disasters are natural phenomena that occur directly or indirectly to disturb human life. Disasters can happen anywhere and anytime. Therefore it is necessary to prepare the community in facing disasters, including the school community. Disaster preparedness education needs to be carried out immediately considering that most Indonesians live in disaster-prone areas. The school community is one of the main stakeholders for preparedness against natural disasters. The purpose of this community service is to provide training for students of SMPN I Cimalaka to be prepared as cadres of disaster prepared schools. After the training, 45 students of disaster preparedness cadres at SMPN I Cimalaka have received training for 3 days of disaster preparedness. And the results of the evaluation showed that the participants' knowledge and skills were all good. Disaster preparedness cadre activities are quite active, namely by disseminating disaster preparedness to fellow students in extracurricular activities such as OSIS, Scouts and PMR. In addition, disaster preparedness cadres are also often involved in disaster recognition training by schools.